Mediating role of existential anxity in the relationship between childhood emotional traumas, social support and tendency to change in addicts - Fereshteh Mirzaeinasab; Yasser Rezapour Mirsaleh; Fatemeh Behjati; Narjes Ghasemi (روانشناسی و روانپزشکی شناخت, 2022)
Introduction: Addiction is recognized as one of the major public health concerns around the world, with various negative consequences for individuals and communities. Aim: This study aimed to investigate the mediating role of existential anxiety in the relationship between childhood emotional trauma, social support, and tendency to change in addicts. Method: In this correlational study, structural equation modeling was applied. The study population consisted of male and female addicts, presenting to rehabilitation centers in Yazd Province, Iran, in 2019. Two-hundred addicts were selected using available sampling among individuals presenting to the rehabilitation centers of Yazd Province. To collect data, the Existential Anxiety Questionnaire by Wims et al. (2004), Childhood Injury Questionnaire by Bernstein et al. (1994), Perceived Social Support Scale by Zimet et al. (1988), and Miller and Tunigan’s Change Tendency Questionnaire (1996) were used. Data were analyzed using structural equation modeling, multiple regression analysis, and Pearson’s correlation coefficient test in SPSS-24 and AMOS-24. Results: The results showed that emotional trauma and social support directly reduced and increased the addicts’ tendency to change, respectively (P<0.05). The findings also showed that emotional trauma and social support indirectly affected the addicts’ tendency to change through the mediating role of existential anxiety (P<0.05). Conclusion: The mediating role of existential anxiety in the relationship between childhood emotional trauma, social support and the readiness to change in addicted people was significant, therefore, providing more social support, emotional discharge regarding childhood traumas, along with planning to reduce existential anxiety using psychological interventions can increase the readiness to change and quit in addicted people.